2015
DOI: 10.1111/1365-2435.12609
|View full text |Cite
|
Sign up to set email alerts
|

Heat hardening in a tropical lizard: geographic variation explained by the predictability and variance in environmental temperatures

Abstract: Summary Over the coming decades, our planet will experience a dramatic increase in average temperatures and an increase in the variance around those temperatures leading to more frequent and harsher heat waves. These changes will impact most species and impose strong selection on physiological traits. Rapid acclimation is the most direct way for organisms to respond to such extreme events, but we currently have little understanding of how the capacity to mount such plastic responses evolves. Accordingly, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
100
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 41 publications
(70 reference statements)
14
100
3
Order By: Relevance
“…; Phillips et al. ) and broader meta‐analyses of acclimation (Gunderson and Stillman ) all find that physiological traits typically only shift by 1–2°C in response to acute or sustained environmental shifts (but see meta‐analysis of CT min acclimation in Pintor et al. ), whereas our measurements often differed by up to 12°C (Fig.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…; Phillips et al. ) and broader meta‐analyses of acclimation (Gunderson and Stillman ) all find that physiological traits typically only shift by 1–2°C in response to acute or sustained environmental shifts (but see meta‐analysis of CT min acclimation in Pintor et al. ), whereas our measurements often differed by up to 12°C (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, Phillips et al. () found that one of our target species, L. coggeri , exhibits a marked heat hardening response. However, they also found that organisms in environments that are already approaching thermal limits have a reduced capacity to shift heat tolerance, which has also been observed in flies (Kristensen et al.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, many other thermal traits are regularly measured in ectotherms, including the optimal temperature and performance breadth for whole‐animal performances (e.g. sprint speed and gut passage time), critical thermal minimum, and heat shock response (Angilletta et al , Clusella‐Trullas, S. et al , Phillips et al , ). Given the pressing need to understand how species adjust to different climates, studying the interactions between these traits and their association with thermoregulatory behavior and thermal environment should be a high priority.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, rapid plastic and evolutionary responses to global climate change have already been observed across taxa ranging from migratory birds (Gill et al 2013) to anadromous fish (Kovach et al 2012), arthropods (Krehenwinkel et al 2016), annual plants (Franks et al 2016), and soil (Bataillon et al 2016) and aquatic invertebrates (Oexle et al 2016). In fact, rapid, directional climatic changes may even facilitate rapid responses (Phillips et al 2016). Thus, although niche conservatism may ultimately constrain the extent and rate at which populations can adapt evolutionarily to climate change (Quintero and Wiens 2013), rapid climate-driven adaptations may not be as rare as once thought (Moran and Alexander 2014).…”
Section: Asynchronous Regimes and The Potential For Rapid Adaptationmentioning
confidence: 93%